Confronting Challenges in Islamic Studies - Brian Wright (International Institute of Islamic Thought, 2017)
At the 2016 meeting of the American Academy of Religion in San Antonio, the International Institute of Islamic Thought (IIIT) hosted the third annual Ismail al Faruqi Memorial Lecture. Delivered by Ahmad Atef Ahmad (University of California Santa Barbara), the lecture focused on the changing academic field of Islamic studies: where the field has been, where it is now, and where it should go in the future. Ahmad began by outlining the history of approaching both Islamic studies and comparative religion in general. After decades of claiming neutrality, he believes that the field has now reached a new phase. “In the past there was an assumption that there is a neutral, global set of rules and tools that can help us understand religion, like those of philosophy or anthropology. However, over time we have come to realize that these tools are in no way neutral and come with their own kinds of baggage.” This failure of neutrality has particularly affected scholars of Islam, because “You find that Muslim scholars who take their primary sources seriously find the deck stacked against them, especially for those who are working in the West and trying to engage in conversations with other religious traditions.” As a result of the realization that the tools of religious studies cannot be neutral, academia has undergone a significant shift ...